THE CONSTRUCTION OF MALE SEXUALITY IN THE MOVIE TINY TIMES - Ika Fatmawati (Universitas Islam Negeri Raden Intan Lampung, 2025)
Sexuality is often related to the female body, but this time in the film Tiny Times, we will try to explore related to the representation of the male body. This study aims to analyze the construction of male sexuality in the film Tiny Times (2013–2015) by Guo Jingming through a qualitative approach and critical discourse analysis method. The focus of the research is directed at three main aspects: the forms of male sexuality displayed, the social and cultural factors that influence the construction, and the implications of these representations on the understanding of masculinity in Chinese popular culture. The findings of the study show that the film represents male sexuality in various forms, ranging from dominant hegemonic masculinity, to alternative masculinity that is more emotional and aesthetic. Male sexuality in this film is influenced by social class factors, urban modernity, cultural capitalism, and contemporary gender values. The representation reflects the negotiation between patriarchal tradition and consumptive modernity that places the male body as a performative object as well as a status symbol. This research confirms that popular media such as Tiny Times not only reflect social realities, but also play a role in shaping gender and sexuality ideologies in society. Keywords: Construction, Male sexuality, Tiny Times Movie.